A Statistical Model of Inner Magnetospheric Electron Density: Van Allen Probes Observations - Jing‐Tian Lv; Xiao‐Xin Zhang; Fei He; Rui‐Lin Lin (Space Weather)
Abstract Based on electron density observations between September 2012 and July 2019 from the Electric and Magnetic Field Instrument Suite and Integrated Science (EMFISIS) on board the Van Allen Probes (VAPs) spacecraft, this paper makes a statistical investigation on the distribution of inner magnetospheric electron density in the magnetic equatorial plane (MEP) under different Kp levels, and further develops a new model of inner magnetospheric electron density in the MEP with multi‐parameters (Kp, SYM‐H, Pdyn, F10.7). The statistical results show that the plasmaspheric electron density in the inner magnetosphere in the MEP has an obvious Magnetic Local Time (MLT) distribution characteristic. With the increase of Kp index, the asymmetrical distribution of plasmaspheric electron density in the MEP increases, reaching the maximum value of erosion at MLT = 02:00, and the erosion at MLT = 14:00 is much less than that at MLT = 02:00. The distribution of plasmaspheric electron density in the low L‐value (L is shell parameter) region (L ≤ 2.8) is less affected by the geomagnetic activity than that in the high L‐value region (L ≥ 3.6). Comparison between the model outputs and the VAP's observations indicates that this statistical model could accurately describe the dynamic distribution characteristics of plasmaspheric electron density in the MEP during geomagnetic storms, such as erosion and refilling, and can be applied to space weather forecast.